Partnership in action: a satellite program to expand an existing bachelor of science in nursing education program. - Boyle A; Davis H; Prithcard HK; McBride M; Orsi A; Scott S; Kresge L (Nurse Educator)
The nursing shortage affects communities at many levels, from community hospitals to schools of nursing. The authors describe an innovative 4-way partnership involving a community healthcare district, a community hospital, a community college, and a state university. Working together, these partners established a new baccalaureate nursing program based at a community college and also functioning as a satellite of an existing university-based program, which increased the enrollment of baccalaureate nursing students by 50%. Their work could serve as a model for other collaborative efforts to expand nursing education and reduce the shortage of nurses.